The Apocalypse of Empire - Shoemaker, Stephen J.
1 online resource (269 pages)
Keywords: Stephen J. Shoemaker argues that earliest Islam was a movement driven by urgent eschatological belief that focused on the conquest, or liberation, of the biblical Holy Land and situates this belief within a broader cultural context of apocalyptic anticipation that includes early Byzantine Christianity, Judaism, and Sasanian Zoroastrianism.